Recent advances in environmental application of activated carbon from banana peel (Musa paradiasaca) in removal of heavy metals from kali asem river water - Verdino, Fadhel; Sari, Putri Anggun; Riyadi, Agus (Jurnal Pelita Teknologi, 2025)
The rapid growth of industry often brings an increase in waste containing heavy metals such as Fe, Pb, Zn, Al, and Cu, which are toxic and pose a threat to environmental sustainability. Kali Asem, a tributary of the Bekasi River flowing through Bantargebang, Bekasi City, is one of the affected areas due to the high waste burden from the TPST Bantargebang and TPAS Sumurbatu. Preliminary studies have shown that the river water contains iron (Fe) and manganese (Mn) levels that exceed the quality standards. Adsorption is one of the effective methods to reduce heavy metal concentrations in wastewater. Currently, bio-based adsorbents made from fruit and vegetable waste are gaining popularity due to their eco-friendly nature, affordability, renewability, ease of synthesis, and high efficiency. Banana peels (Musa paradisiaca), in particular, contain cellulose that can be processed into activated carbon for use as an adsorbent. This study aims to evaluate the effectiveness of activated carbon derived from kepok banana peels in reducing Fe and Mn concentrations in Kali Asem river water. The research uses an experimental method with a focus on measuring Fe and Mn levels before and after treatment.